A city in a bunker in a city: Demilitarizing art in South Korea. (15th February 2023) - Gitzen, Timothy
Abstract: Located mere feet from the busy Yeouido Bus Transfer Center, the Seoul Museum of Art (SeMA) Bunker is a former military bunker from 1970s authoritarian South Korea that now showcases changing art exhibits. Debuting in November 2019, Paju (by artist Kim Seung Rea) features a series of paintings and statues capturing life in the town of Paju in the Geyeonggi Province near the border of the Demilitarized Zone (DMZ) that separates North and South Korea. As a critique of militarization, Paju not only offers a glimpse into the life that blossoms amidst the guard towers, bulwarks, and barbed wire, it challenges the power dynamic implicit in the space of the bunker. Cold War ideologies overlap in SeMA Bunker, for while the bunker was purportedly designed to keep the former president, Park Chung‐hee, safe during potential North Korean attack, the town of Paju was to act as human and infrastructural sacrifice to keep the rest of the country secure. Therefore, to bring Paju into the bunker via the exhibit is to inverse that power relationship and thus work to demilitarize the space, the town, and ultimately the patrons.